Stability of mortiño dye (Vaccinium floribundum) for the application in a food matrix - Recalde Calderón, Melanie Jessenia (2025)
Andean blueberry (Vaccinium floribundum) is a wild fruit from the Andes recognized for its high anthocyanin content, bioactive compounds with antioxidant properties and potential application as natural colorants in the food industry. This study studied the stability of the pigment extracted from this fruit under different temperatures, pH, and storage conditions to evaluate its viability as an alternative to synthetic colorants. To preserve the sensitive compounds and facilitate their subsequent extraction, the fruit was pretreated with ultra-freezing and lyophilization. A solid-liquid extraction with 96% ethanol acidified with citric acid was subsequently performed, obtaining the pigment in liquid form. The pigment was then incorporated into a yogurt-type food matrix for instrumental and sensory analysis. The results showed that the highest retention of the pigment was achieved at pH 4 and a temperature of 4°C, with a progressive degradation of the pigment over time, with the greatest loss occurring at week 4. Statistical analysis revealed significant differences between treatments according to ANOVA and Tukey tests. The yogurt application showed perceptible differences in colorimetry, highlighting greater intensity in the a* (red) coordinates and lower in the b* (yellow) coordinates compared to commercial yogurt. It is concluded that the Andean blueberry pigment presents adequate stability under acidic and low-temperature conditions, making it a viable alternative for use as a natural food colorant, thus contributing to healthier products with a clean label.